2015
DOI: 10.1016/j.ijpara.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Amblyomma americanum tick Serpin19, an inhibitor of blood clotting factors Xa and XIa, trypsin and plasmin, has anti-haemostatic functions

Abstract: Tick saliva serine protease inhibitors (serpins) facilitate tick blood meal feeding through inhibition of protease mediators of host defense pathways. We previously identified a highly conserved Amblyomma americanum serpin (AAS) 19 that is characterized by its reactive center loop being 100% conserved in ixodid ticks. In this study, biochemical characterization reveals that the ubiquitously transcribed AAS19 is an anti-coagulant protein, inhibiting the activity of five of the eight serine protease blood clotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(100 citation statements)
references
References 140 publications
(150 reference statements)
6
92
1
Order By: Relevance
“…In another study we showed that AAS19 mRNA was expressed in multiple tick organs, and that native AAS19 was an immunogenic tick saliva protein as indicated by antibodies to replete fed tick saliva proteins specifically binding yeast expressed rAAS19. Further, we showed that rAAS19 has anti-haemostatic functions and that it is an inhibitor of trypsin-like proteases including five of the eight serine proteases in the blood clotting cascade (Kim et al, 2015a). These earlier findings collectively suggested the potential for AAS19 to regulate important functions in tick feeding success.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In another study we showed that AAS19 mRNA was expressed in multiple tick organs, and that native AAS19 was an immunogenic tick saliva protein as indicated by antibodies to replete fed tick saliva proteins specifically binding yeast expressed rAAS19. Further, we showed that rAAS19 has anti-haemostatic functions and that it is an inhibitor of trypsin-like proteases including five of the eight serine proteases in the blood clotting cascade (Kim et al, 2015a). These earlier findings collectively suggested the potential for AAS19 to regulate important functions in tick feeding success.…”
Section: Discussionmentioning
confidence: 99%
“…Of significant interest to us, the antibody response to rAAS19 also reacted with epitopes on glycosylated and non-glycosylated forms of native AAS19 as revealed by western blotting analysis data. The observation that native AAS19 protein is present in multiple tick organs and the fact that ticks inject this protein into the host during feeding (Kim et al, 2015a) suggests that this protein may function inside the tick and at the tick-feeding site. This observation is not unique to AAS19.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations